Experimental study on the effects of sprinkler activation on the stratified smoke layer inside a 36 m2 enclosure. (May 2021) - Vetter, M.; Dinkov, I.; Schelb, D.; Trimis, D.
Abstract: Experiments have been carried out in a specially designed 36 m 2 compartment. The experimental results show the main phenomena during the fire and smoke propagation in the compartment before sprinkler activation and additionally the interaction between the hot flue gases in the smoke layer and the water spray. The axial temperature profiles at three characteristic positions inside the compartment were measured. A comparison of a standard sprinkler and a High-Pressure Water Mist system (HPWM) revealed two different phenomena, which are flue gas scrubbing and recirculation motion, respectively – both eventually leading to an increased smoke obscuration inside the compartment. Highlights: Formation of the stable smoke layer due to the combustion process could be observed. Flue gas scrubbing due to the high specific drop loading after sprinkler activation. Diluted flue gas recirculation after High-Pressure Water Mist (HPWM) activation. Gradual dilution of smoke and finally complete dissolution of stratified smoke layer.